Interest Rate Spillovers from the United States: Expectations, Term Premia and Macro-Financial Vulnerabilities - Aaron Mehrotra; Richhild Moessner; Chang Shu (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyse how movements in the components of sovereign bond yields in the United States affect long-term rates in 10 advanced and 21 emerging economies. The paper documents significant global spillovers from both the expectations and term premia components of long-term rates in the United States. We find that spillovers to domestic long-term rates in emerging economies from the US expectations components tend to be more sizeable than those from the US term premia. Finally, spillovers from US term premia are larger when an emerging economy displays greater macro-financial vulnerabilities.
Keywords: E52; E43; F42; F65; 330; interest rate spillovers; term premia; emerging economies